Implementasi Super Spring GPS Tracker dalam pengungkapan kasus curanmor (Studi Satreskrim Polrestabes Bandung) - Syafirudin, Muhamad Ardiriansyah Nurfauzan (Advances in Police Science Research Journal, 2020)
This study is motivated by the high number of cases of motor vehicle theft (curanmor) that occurred at Capital Subregional Police (Polrestabes) Bandung from 2016 to 2020. Based on data from the Criminal Investigation Unit (Satreskrim) of Polrestabes Bandung, total crime is not comparable with crime clearance obtained. Police attempts include inspection and investigation of the crime in accordance with the Regulation of the Head of the Indonesian National Police number 6 of 2019 concerning the criminal investigation. They are in the form of the Super Spring GPS Tracker implementation program that will help disclose curanmor cases and reduce the number of curanmor cases. The study aims at describing the implementation of the Super Spring GPS Tracker in helping curanmor cases, as well as informing the stages of use and factors that influence. This study used a qualitative approach and data collection techniques of interviews, observations, and document review. The results of the study found that the utilization of manual method is not optimal because, in many implementations, it is not in accordance with the Standard Operating Procedures (SOP). Analysis of the implementation of the Super Spring GPS Tracker in helping to disclose curanmor cases will maximize the settlement of these cases. The research findings show the factors that support the implementation of the Super Spring GPS Tracker are the budget, members and community participation factors. Based on the results of the study, the suggested recommendation is that the Head of Police Resort (Kapolres) communicate with the Unit Head of Criminal Investigation Unit (Kasat Reskrim) to discuss the Super Spring GPS Tracker implementation program, conducting socialization to the public prior to the implementation of the Super Spring GPS Tracker and the results of its implementation, conducting a collaboration with companies and vehicle dealers in Bandung to support the program, adding Satreskrim personnel in accordance with the List of Personnel at the Subregional Police (Polres) level. Keywords: Implementation, Super Spring GPS Tracker, disclosure, curanmor, Bandung Polrestabes.